In Vitro Antifungal Screening of Argentine Native or Naturalized Plants against the Phytopathogen Monilinia fructicola - Stegmayer, María Inés; Fernández, Laura Noemí; Álvarez, Norma H.; Seimandi, Gisela Marisol; Reutemann, Andrea Guadalupe; Derita, Marcos Gabriel (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: One of the main problems that fruit health has gone through in recent years is the problematic eradication of their fungal pathogens during crops or the post-harvest stage. This concerns the whole world because it represents huge production losses, fruit export restrictions, and consumer distrust. Consequently, new alternatives are sought to avoid the increasing use of fungicides that cause important damage to fruit consumers and the environment. One of the alternatives to solve this problem could be exploring plants and their active compounds applied to the treatment of fruit health. Materials and Methods: This article describes peach production worldwide and particularly in Argentina, in addition to the main fungal rot that causes the greatest economic losses. Furthermore, experimental in-vitro studies of 69 extracts obtained from 18 plants growing in the central region of Argentina were displayed against the devastating fungus Monilinia fructicola, which greatly affects stone fruits. A simple and effective method developed in agar plate was applied to evaluate a large number of samples in a short time. Results: The results showed that approximately 36% of the samples tested were strongly active against this pathogen, 12% were moderately active, and 52% demonstrated to be inactive. Conclusion: These findings support the possible use of natural products for fruit health and the importance of deepening in this field of science.
Keywords: phytopathogenic